Carbono e nitrogênio em solos e metais pesados em serapilheiras de florestas urbanas da cidade de São Paulo, SP - Ramon, Mauro (2018)
Urban forests are important sites that promote ecosystem services, such as sequestration and stocking of carbon (C) and nitrogen (N), as well as serving as a reservoir for biodiversity. One of the main compartments responsible for nutrient cycling in these forests is the litter layer, which also hosts a wide variety of microorganisms and has a close relationship with the soil compartment in ecosystem processes. Normally, these forest fragments are surrounded by avenues of intense vehicular traffic, which emits a great amount of atmospheric pollutants. Among the main pollutants, it is possible to emphasize heavy metals, which are very toxic to microfauna and soil flora. Some studies have shown the relevance of urban forests as a means of mitigating anthropogenic impacts, highlighting the importance of getting to know the dynamics and the functioning of these forests. The objective of this work was to determine the concentration of carbon and nitrogen in different soil layers, different points within each forest and along four forest fragments in the city of. In addition, this work also aimed to evaluate the deposition of heavy metals in the litter of these same forests. Four urban forests were selected in a center-periphery sense, which also vary in size and shape. Samples of litter were collected for analysis of arsenic (As), cadmium (Cd) and copper (Cu) and soil samples for carbon and nitrogen analysis. Considering the results obtained, it was noticed that the concentrations of carbon and nitrogen in urban forest soils were higher in the parks more to the center of the urban nucleus of the city of São Paulo, being smaller for the more peripheral parks. Regarding the heavy metals in the litters, there was a trend of this same gradation of concentrations, less for the element cadmium. This study brings some contributions in the understanding of biogeochemical cycles in urban forest systems. In addition, this work shows that the Trianon Park is the most anthropized, with differentiated conditions of soil texture and consequently in the C and N stocks, as well as higher concentrations of Cu and As adsorbed in the litter beds analyzed. This study provides a quantitative assessment of comparisons of urban forests in a metropolis, with results that may aid in public policies in municipal, state and federal legislation. Soil verification, in all its factors, such as texture and density, should be made to manage urban forests that retain higher concentrations of C and N, aiding in the mitigation of greenhouse gases and better provision of ecosystem services.